Dynamic Double Kinetic Resolution of Amines and Alcohols under the Cocatalysis of Raney Nickel/Candida antarctica Lipase B: From Concept to Application. Issue 14 (18th March 2014) - Xia, Bo; Cheng, Guilin; Lin, Xianfu; Wu, Qi
Abstract: Herein, we have established a dynamic double kinetic resolution (DDKR) strategy under the co‐catalysis of Raney nickel and Candida antarctica lipase B (CAL‐B) for the one‐pot simultaneous resolution of primary amines and secondary alcohols (or esters). The DDKR strategy was successfully applied to the resolution of a series of racemic amines and secondary alcohols (or esters) as well as mexiletine, an important antiarrhythmic agent. The catalysts could be recycled and reused several times with the same high activity. Scale‐up experiments were also successful. As a more atom‐economical and efficient process than traditional simple kinetic resolutions, the DDKR strategy can be widely used to prepare optically pure amines and alcohols. Abstract : A dynamic double kinetic resolution (DDKR) strategy under the co‐catalysis of Raney nickel and Candida antarctica lipase B (CAL‐B) was established for the one‐pot simultaneous resolution of primary amines and secondary alcohols.